Utilization Technology Spatial in Making Class Maps Suitability of Mango Plantation Land in Kakas District, East Coast Minahasa - Sandra Pakasi; Diane Pioh; Wiske Rotinsulu; Afra Makalew (Jurnal Syntax Transformation, 2023)
Land suitability evaluation is very important in the process of matching land types for specific uses. This research aims to create map of the distribution of land suitability classes for mango plants in Kakas District using technology Spatial . This research was carried out using field survey and geoprocessing methods . Data collection techniques include: documentation , observation and analysis laboratory . Determination class suitability land use method from FAO ie matching observation variables that is condition grow plant Mango and its qualities / characteristics land . In this study, 22 units were obtained land map (SPL) covering an area of 3927.07 Ha spread over several village in Kakas District . Class map suitability resulting land _ that is class suitability S1 land (very suitable ) for criteria nutrient retention and available nutrients . Whereas criteria temperature and rooting media included in class suitability S2 land ( enough appropriate ) scattered and for criteria water availability and levels danger erosion generally enter the S3 class ( according to marginal) spread across all SPL. Temporary level danger erosion is criteria give class N ( no appropriate ) for plant mango at 10 ( ten ) SPL with area 1351.93 Ha.